2004
DOI: 10.1002/jbm.a.30082
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gene expression in rat bone marrow stromal cells cultured on titanium alloy discs of different roughness

Abstract: Rat bone marrow stromal cells were cultured on either Ra (0.14 microm) or Ra (5.8 microm) Ti6Al4V discs for 24 or 48 h. Cells on the Ra (0.14 microm) surface showed typical fibroblastic morphology, whereas cells on the Ra (5.8 microm) surface were in clusters with a more epithelial appearance. RNA was extracted from the cells at both time points, and gene expression was analyzed by using a rat gene microarray. At 24 and 48 h, a similar number of genes were both up- and down-regulated at least twofold on the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…The powder-based 3D printing process enabled us to create structures with a high surface roughness. In literature, the influence of surface roughness on cell attachment and proliferation is described mainly in conjunction with grinded surfaces and is discussed controversial [17]. When trying to relieve cells from our HA-S with Trypsin in preliminary studies, we observed very strong cell attachment.…”
Section: Discussionmentioning
confidence: 93%
“…The powder-based 3D printing process enabled us to create structures with a high surface roughness. In literature, the influence of surface roughness on cell attachment and proliferation is described mainly in conjunction with grinded surfaces and is discussed controversial [17]. When trying to relieve cells from our HA-S with Trypsin in preliminary studies, we observed very strong cell attachment.…”
Section: Discussionmentioning
confidence: 93%
“…39 In addition, they produce higher levels of growth factors and cytokines that regulate osteogenesis including PGE2, which is required for their differentiation, 40,41 and osteoprotegerin, 42 which can modulate osteoclastic bone resorption. 43 Similarly, osteoblastic differentiation of bone marrow stromal cells and fetal rat calvarial cells is also surface dependent, [44][45][46] but the role of surface properties on differentiation of isolated human MSCs was not previously examined. While we did not address this question directly, our results suggest that surface-dependent changes in MSCs make them more sensitive to BMP-2, and the BMP-2-treated cells are more responsive to PEMF.…”
Section: Discussionmentioning
confidence: 99%
“…on day 7 after fracture, GFP-and von Kossa-positive cells were observed around the titanium screws of the fixation plate. Several studies have reported that titanium stimulates osteoblastic differentiation in mesenchymal and osteoblastic cells [10,12,13,26]. For example, Wall et al [26] reported that titanium surfaces accelerate osteogenic differentiation of mesenchymal stromal cells in vitro.…”
Section: Discussionmentioning
confidence: 99%